The IntAct database: efficient access to fine-grained molecular interaction data. Issue Volume 50:Issue D1(2022) (11th November 2021) - del Toro, Noemi; Shrivastava, Anjali; Ragueneau, Eliot; Meldal, Birgit; Combe, Colin; Barrera, Elisabet; Perfetto, Livia; How, Karyn; Ratan, Prashansa; Shirodkar, Gautam; Lu, Odilia; Mészáros, Bálint; et al.
Abstract: The IntAct molecular interaction database (https://www.ebi.ac.uk/intact ) is a curated resource of molecular interactions, derived from the scientific literature and from direct data depositions. As of August 2021, IntAct provides more than one million binary interactions, curated by twelve global partners of the International Molecular Exchange consortium, for which the IntAct database provides a shared curation and dissemination platform. The IMEx curation policy has always emphasised a fine-grained data and curation model, aiming to capture the relevant experimental detail essential for the interpretation of the provided molecular interaction data. Here, we present recent curation focus and progress, as well as a completely redeveloped website which presents IntAct data in a much more user-friendly and detailed way.